Estimating Patient Survival and Risk of End-Stage Kidney Disease in Patients With Autosomal Dominant Polycystic Kidney Disease in Iran (Iranian Journal of Kidney Diseases, 2023)
Introduction. Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary kidney disease that can affect several organs. The clinical course of the disease varies among patients; some never become symptomatic, and others reach end-stage kidney disease (ESKD) in the 5th decade of their life. Methods. This historical cohort study was conducted on ADPKD patients to investigate kidney and patient survival rates and related risk factors in Iran. Survival analysis and risk ratio calculation were performed using the Cox proportional hazards model, Kaplan– Meier method, and log-rank test. Results. Among the 145 participants, 67 developed ESKD, and 20 died before the end of the study period. Developing chronic kidney disease (CKD) at the age of ≤ 40, baseline serum creatinine level (SCr) of more than 1.5 mg/dL, and cardiovascular disease increased the risk of ESKD by 4, 1.8, and 2.4 times; respectively. Patient survival analysis revealed a fourfold increase in mortality if the glomerular filtration rate (GFR) declined more than 5 cc/min annually and if CKD was diagnosed at the age of ≤ 40. Vascular thrombotic events or ESKD in the course of disease increased the risk of death by approximately 6- and 7-fold, respectively. Kidney survival was 48% by the age of 60 and 28% by the age of 70. Patient survival was 86.05% at the age of 60 and 67.99% at the age of 70. Additionally, men had a significantly better renal function and survival than women. Conclusion. Elevated baseline SCr and cardiovascular disease can increase ESKD risk in ADPKD patients. A rapid decline in GFR, ESKD development, and vascular thrombotic events increase the risk of death, but early CKD can affect both.  DOI: 10.52547/ijkd.7551